PENGELOLAAN MEDIA SOSIAL INSTAGRAM PADA INDUSTRI PARIWISATA (PT GEMILANG MEDIA WISATAMA (TRAVELXISM)).docx - Maulana Yusuf; Rian Andrian; Nuur Wachid Abdulmajid (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2022)
Digital marketing strategies are now widely used with the use of Instagram social media, including in the tourism industry. Therefore, optimal management of Instagram social media is needed so that it can be a means of communication between companies and the public regarding tourism. The purpose of this study is to explain how to manage Instagram social media at PT Gemilang Media Wisatama. The research method in this study uses a qualitative descriptive method that will describe in detail about Instagram social media on the @Travelxism account. The results of the study note that the management of Instagram social media that is carried out every day on the @Travelxism account uploads at least 1 content per day. This certainly cannot be separated from a well-organized content creation process. As for the flow of content creation, there are 6 stages, namely planning, content search, copywriting, content creation, content publication and evaluation stage.